HUBUNGAN ANTARA KONTROL DIRI DAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA - Kezia Puspitha Evav Lobwaer; Doddy Hendro Wibowo (Bajang Institute, 2023)
Adolescence is a transition period from childhood to adulthood and is a vulnerable period. Adolescents have a tendency to be curious and want to try everything new, so they need the ability to control their behavior towards the stimuli they receive so that deviant actions do not occur which can have a bad impact, one of which is premarital sexual behavior. This research aims to determine the relationship between self-control and premarital sexual behavior in adolescents using quantitative correlational design methods and incidental sampling techniques. The samples taken were 100 teenage students. The scales used for data collection are the sexual behavior scale and the self-control scale (SCS). The results obtained in this research show that Rxy = -0.180 and sig = 0.036, which means that there is a negative relationship between self-control and premarital sexual behavior in adolescents. The results of the research provide the implication that the way to prevent sexual behavior in adolescents is to train and improve their ability to control themselves